(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The information on microclonal propogation of two species of Ferula L.: Ferula tadshikorum Pimenov and Ferula sumbul (Kauffm.) Hook.f. (Apiaceae Lindl.), and two species of Ungernia Bunge: Ungernia sewertzowii (Regel) В.Fedtsch. and Ungernia victoris Vved. Ex Artjush (Amaryllidaceae J.St.-Hil.), and about the issues which arise in microclonal propogation, and particularly in microclonal propogation of these four valuabla medicinal plant species.